Co-immobilization of Rhizomucor miehei lipase and Candida antarctica lipase B and optimization of biocatalytic biodiesel production from palm oil using response surface methodology. (October 2019) - Shahedi, Mansour; Yousefi, Maryam; Habibi, Zohreh; Mohammadi, Mehdi; As'habi, Mohammad Ali
Abstract: Lipases from Candida antarctica B (nonspecific lipase) and Rhizomucor miehei (1, 3-specific lipase) were simultaneously immobilized on epoxy functionalized silica gel under mild conditions. The results showed rapid and simple immobilization of 4–15 mg of CALB:RML (different ratios 4:1, 2:1, 1.5:1, 1:1) on 1 g of support after 6 h. The thermal stability of derivatives and also their stability in methanol were greatly improved compared to the single immobilized enzyme. All the derivatives were also used to catalyze the transesterification of palm oil with methanol to produce fatty acid methyl esters (FAMEs). Response surface methodology (RSM) and a central composite rotatable design (CCRD) was used to study the effects of five factors, reaction temperature, methanol/oil ratio, reaction time, t -butanol concentration and CALB:RML ratio on the fatty acid methyl esters (FAME) yield. A quadratic polynomial equation was obtained for methanolysis reaction by multiple regression analysis. The optimum combinations for the reaction were CALB:RML ratio (2.5:1), t -butanol to oil (39.9 wt%), temperature (35.6 °C), methanol:oil ratio (5.9), reaction time 33.5 h. FAME yield of 78.3.5%, which was very close to the predicted value of 75.2%, was obtained. Verification experiment confirmed the validity of the predicted model. Highlights: Lipases from Candida antarctica B and Rhizomucor miehei were simultaneously immobilized on silica. The thermal stability of derivatives and also their stability in methanol were greatly improved. All the derivatives were used to catalyze the transesterification of palm oil with methanol to produce biodiesel. The increasing the amount of CALB relative to RML resulted to improving the thermal and methanol stability and FAME yield.